2016
DOI: 10.1038/ncb3363
|View full text |Cite
|
Sign up to set email alerts
|

The polycystin complex mediates Wnt/Ca2+ signalling

Abstract: WNT ligands induce Ca2+ signaling on target cells. PKD1 (Polycystin 1) is considered an orphan, atypical G protein coupled receptor complexed with TRPP2 (Polycystin 2 or PKD2), a Ca2+-permeable ion channel. Inactivating mutations in their genes cause autosomal dominant polycystic kidney disease (ADPKD), one of the most common genetic diseases. Here, we show that WNTs bind to the extracellular domain of PKD1 and induce whole cell currents and Ca2+ influx dependent on TRPP2. Pathogenic PKD1 or PKD2 mutations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 63 publications
5
133
0
Order By: Relevance
“…The renal tissues in Vil Cre Pkd2 f/f mice have elevated levels of active, nuclear, and total β-catenin (Ctnnb1) proteins ( Figure 1, A and B) and Axin2, c-Myc, and cyclin D1 proteins, which are produced by Wnt target genes ( Figure 1, C and D), compared with control mice (Pkd2 f/f ). These results are consistent with previous reports that PC2 deficiency increases Wnt/β-catenin signaling (27,37,66 Figure 2A). The loss of one Ctnnb1 allele rescued the elevated levels of active, nuclear, and total β-catenin found in the kidneys of Vil Cre Pkd2 f/f mice, bringing the levels down almost to those of control Pkd2 f/f mice, which did not have Vil-Cre ( Figure 1, A and B).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The renal tissues in Vil Cre Pkd2 f/f mice have elevated levels of active, nuclear, and total β-catenin (Ctnnb1) proteins ( Figure 1, A and B) and Axin2, c-Myc, and cyclin D1 proteins, which are produced by Wnt target genes ( Figure 1, C and D), compared with control mice (Pkd2 f/f ). These results are consistent with previous reports that PC2 deficiency increases Wnt/β-catenin signaling (27,37,66 Figure 2A). The loss of one Ctnnb1 allele rescued the elevated levels of active, nuclear, and total β-catenin found in the kidneys of Vil Cre Pkd2 f/f mice, bringing the levels down almost to those of control Pkd2 f/f mice, which did not have Vil-Cre ( Figure 1, A and B).…”
Section: Resultssupporting
confidence: 83%
“…Previous studies showed that PC2 in association with Wnt signaling induces calcium influx and that the loss of PC2 disturbs polarization during directional cell migration (27,37,76). The present study demonstrated the importance of elevated Wnt/β-catenin signaling in the polycystic kidney disease phenotypes caused by a Pkd2 loss-of-function mutation in mice.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…A recent study proposed that PC1 is a coreceptor for noncanonical Wnt signaling (47). These data may suggest an indirect functional ) loss-of-function alleles (nonsense, frameshift, splice site) was compared with the expected burden independent of ethnicity, and that in the European subset of discovery cohort cases (n = 92) was compared with that in European controls (n = 3,274) using existing scripts and statistical tests listed below.…”
Section: Discussionmentioning
confidence: 99%